Motion to develop justification of a sentence lodged before a sentence has been passed (Ius Novum, 2021)
The article presents the assessment of the court practice of dealing with a motion to develop justification of a sentence lodged before a sentence has been passed. To that end, the normative material and the Supreme Court case law have been subject to critical interpretation. On the other  hand,  what  provided  the  impulse  to  write  this  article  was  that  the  problem,  which  seemed to have been solved a long time ago, was referred to in the judgement of the European Court  of  Justice  of  20  november  2018  in  the  case  Witkowski  v.  Poland  in  the  context  of  an  individual’s  right  of  access  to  a  court  protected  by  the  Constitution  and  the  Convention. The  considerations  presented  in  the  article  refer,  inter  alia,  to  irrelevance,  inadmissibility  and  inefficiency  of  the  application  and,  as  a  result,  confirm  the  preliminary  thesis  that  the court  proceedings  concerning  a  motion  to  develop  justification  of  a  sentence  before  it  has  been passed had been inappropriate. At the same time, the article provides a solution to the problem that consists in the assessment of the procedural step referred to in the title from the perspective of the moment when the decision on the matter is being taken and not the moment it was done. As a result, if at the time a motion to develop justification of a sentence lodged before a sentence has been passed is dealt with before a sentence has been passed, the step, as having no procedural significance, should only result in a technical activity of including the motion in the case files. However, in case a sentence subject to justification has been already passed, the issue of the moment when the motion was lodged is irrelevant to its admissibility. The above-mentioned solution is in conformity with the judgement of the European Court of Justice in the case Witkowski v. Poland.
Keywords: trial; motion to develop justification; Witkowski v. Poland; formal deficiencies in a motion; motion inefficiency